Pelatihan Perencanaan & Penyelenggaraan Festival Budaya bagi Masyarakat di Desa Wisata Sayan, Bali - Putu Surya Laksana Rahjasa; Made Darmiati; Ni Putu Evi Wijayanti; Putu Ayu Aryasih (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2022)
In order to restore the tourism sector in Sayan village, the local government coordinates with the community and other stakeholders at the village level, by carrying out activities/ programs that support tourism such as: village object development, building supporting facilities, fostering/providing counseling and training to the community and organize events, to restore the level of tourist visits to the Sayan village. The closest activity that is planned to be held by the Sayan tourist village to increase the level of tourist visits to its tourist village is the holding of a cultural festival event. Seeing the need for developing the quality of human resources needed by the Sayan tourism village in planning and packaging the cultural festival event that will soon be held, it is deemed necessary to carry out training with a focus on planning and packaging festival events for the Sayan village community which is carried out by the D4 Travel Business Management Study Program, Bali Tourism Polytechnic as a form of community service. The result of this training is a change in the understanding of the trainees in preparation for designing and organizing cultural festivals in the Sayan tourist village.